Accuracy of different oxygenation indices in estimating intrapulmonary shunting at increasing infusion rates of dobutamine in horses under general anaesthesia. Issue 3 (June 2015) - Briganti, A.; Portela, D.A.; Grasso, S.; Sgorbini, M.; Tayari, H.; Bassini, J.R. Fusar; Vitale, V.; Romano, M.S.; Crovace, A.; Breghi, G.; Staffieri, F.
Highlights: Dobutamine infusion profoundly affects oxygen extraction in horses anaesthetised with isoflurane. All the OTIs tested in this study demonstrated a poor correlation with the Qs/Qt. F-shunt is the most reliable OI for the estimation of Qs/Qt independent of the haemodynamic conditions of the patient. OTIs should be used cautiously in horses under isoflurane anaesthesia. Abstract: The aim of this study was to evaluate the correlation of commonly used oxygenation indices with venous admixture (Qs/Qt) in anaesthetised horses under different infusion rates of dobutamine. Six female horses were anaesthetised with acepromazine, xylazine, diazepam, ketamine, and isoflurane, and then intubated and mechanically ventilated with 100% O2 . A Swan–Ganz catheter was introduced into the left jugular vein and its tip advanced into the pulmonary artery. Horses received different standardised rates of dobutamine. For each horse, eight samples of arterial and mixed venous blood were simultaneously obtained at fixed times. Arterial and venous haemoglobin (Hb) concentration and O2 saturation, arterial oxygen partial pressure (PaO2 ), venous oxygen partial pressure (PvO2 ), and barometric pressure were measured. Arterial (CaO2 ), mixed venous (CvO2 ), and capillary (Cc′O2 ) oxygen contents were calculated using standard formulae. The correlations between F-shunt, arterial oxygen tension to fraction of inspired oxygen ratio (PaO2 /FiO2 ), arterial to alveolar oxygen tension ratio (PaO2 /PAO2 ), alveolar to arterial oxygen tension difference (P[A − a]O2 ), and respiratory index (P[A − a]O2 /PaO2 ) were tested with linear regression analysis. The goodness-of-fit for each calculated formula was evaluated by means of the coefficient of determination ( r 2 ). The agreement between Qs/Qt and F-shunt was analysed with the Bland–Altman test. All tested oxygen tension-based indices were weakly correlated ( r 2  < 0.2) with the Qs/Qt, whereas F-shunt showed a stronger correlation ( r 2  = 0.73). F-shunt also showed substantial agreement with Qs/Qt independent of the dobutamine infusion rate. F-shunt better correlated with Qs/Qt than other oxygen indices in isoflurane-anaesthetised horses under different infusion rates of dobutamine.